Critical Reflections on Pro-Poor Tourism and Local Communities` Participation at Grass-Roots Level: The Case of Chimanimani District, Zimbabwe - Zibanai Zhou (IGI Global, 2022)
This chapter investigated the extent to which pro-poor tourism benefits are trickling down to the most deserving people in Chimanimani district, Zimbabwe. This chapter critically reflects on pro-poor tourism construct, community tourism development models, community participation and involvement, tourism benefit sharing scheme, and community livelihood in the context of a rural community. A questionnaire survey and focus group discussions were used to collect data. Embedded in the neoliberal and post-modernist perspectives, the chapter established huge potential for the Chimanimani community to benefit from pro-poor tourism. There is even more scope to enhance tourism benefits if the community`s tourism model, extent of participation, empowerment, and tourism benefits sharing scheme are recalibrated.